CLINICAL SPECTRUM AND MANAGEMENT OUTCOMES OF SUPRARENAL MASSES IN INFANTS: A 17-YEAR TERTIARY CENTER EXPERIENCE - Milosevic, Goran; Ilic, Olga; Lazic, Jelena; Krstovski, Nada; Jankovic, Srdja; Krcunovic, Jelena; Svorcan, Jovana; Kostadinovic, Jovana; Radovic, Tijana; Pavlovic, Djordje; Rodic, Predrag (Medical Research, 2026)
Introduction/Aim: The detection of suprarenal masses (SRM) in neonates and infants has increased due to widespread prenatal and postnatal ultrasonography. While surgery was historically the standard treatment, a conservative approach is now advocated for small, asymptomatic masses. This study aimed to analyze the management and clinical outcomes of SRM at a single tertiary care center over the last two decades. Material and Methods: Retrospective analysis of 39 patients diagnosed with SRM between 2006 and 2023 was conducted. Clinical, radiological (US, CT, MRI), and laboratory data (urinary VMA/HVA, NSE) were evaluated. The follow-up protocol consisted of ultrasonography every two weeks during the first three months of age, followed by monthly or quarterly evaluations until complete resolution, with a median follow-up of 16.6 months (range: 1.9–89). Patients were managed via upfront surgery or a conservative protocol. Results: SRM larger than 5 cm were identified in 18% of patients (7/39), out of which five underwent surgery confirming neuroblastoma (NBL) and in remaining two patients spontaneous resolution of mass occurred. For the 32 patients with masses smaller than 5 cm, a conservative approach was initially adopted. Eight of these patients (25%) eventually required surgery, due to elevated urinary catecholamines, which proved to be a reliable indicator of NBL. Complete regression was observed in all other cases managed conservatively. Conclusion: Close observation of small SRM is safe in carefully selected patients and effectively reduces unnecessary surgical interventions. Urinary catecholamine metabolites remain a valuable tool for identifying high-risk patients requiring surgical treatment.